255 CARDIAC MRI: DETECTION OF MI IN ISCHEMIC, NONISCHEMIC, AND MIXED CARDIOMYOPATHY. (1st January 2005) - Kaushal, R.; Fieno, D.; Radin, M.; Shaoulian, E.; Kadish, A.; Narula, J.; Goldberger, J.; Shivkumar, K.; Bello, D.
Abstract : Introduction: Cardiomyopathies are classified as ischemic (ICM) based on the following clinical criteria: evidence of prior MI, significant coronary stenosis on coronary angiography, and/or prior revascularization. Patients who do not meet these criteria are classified as nonischemic (NICM). Purpose: This study investigated the use of Cardiac MRI (CMRI) to identify evidence of prior MI in patients with severe left ventricular dysfunction of mixed etiologies. Methods: CMRI was performed on 128 patients with severe left ventricular dysfunction. 100 (78%) patients were classified as ICM (mean EF: 29±10%) and 28 (22%) as NICM (mean EF: 31±11%). Two blinded observers evaluated each study. Results: 95 patients (95%) with clinical criteria for ICM demonstrated MI, despite the fact that 32 (32%) of the ICM patients had no history or clinical evidence of prior MI. In contrast 6/28 patients (21%) with NICM demonstrated MI. The mean infarct size as percent of LV mass was 27±18 and 17±13 among ICM and NICM patients, respectively (p=0.12); transmural MI was seen in 57% of ICM patients whereas only 14% of NICM patients had evidence of transmural hyperenhancement (p≤0.001). Table shows the relationship between the extent of CAD based on angiography and the presence or absence of infarct detected by CMRI. 12 patients with ICM were identified with LV dysfunction out of proportion to the extent of CAD. 10 of the 12 patients (83%) had evidence on CMRI of prior MI but had no such history. The mean infarct size was 15±13% of LV mass. Conclusions: In heart failure patients, 95% of patients with severe left ventricular dysfunction satisfying clinical criteria for ICM have evidence of prior MI as identified by contrast-enhanced MRI, with 32% of these patients lacking a history or clinical evidence of prior MI (silent MI). 21% of patients with non-ischemic cardiomyopathy have MRI evidence of prior MI.